EFFECTS OF GUIDED DISCOVERY AND MODEL-LEAD-TEST STRATEGIES ON QUANTITATIVE REASONING SKILLS OF PUPILS WITH LEARNING DISABILITIES IN UYO, NIGERIA (2023)
Quantitative Reasoning Skills (QRS), the ability to apply basic mathematical skills to solve practical life situations, are essential for successful schooling and survival in the society. However, many Pupils with Learning Disabilities (PwLD) in Uyo, Nigeria have low QRS, which partly accounts for their poor performance in mathematics and other life vocations. Previous studies concentrated more on the problem of teaching reading and development of strategies for improving reading skills among PwLD than on intervention to improve their QRS. This study, therefore, was carried out to determine the effect of Guided Discovery Strategy (GDS) and Model-Lead-Test Strategy (MLTS) on QRS of PwLD in Uyo, Nigeria. The moderating effects of gender and mathematics anxiety were also examined. The study was anchored on information Processing Theory, while the pretest-posttest control group quasi-experimental design, with a 3x2x3 factorial matrix was adopted. The multi-stage sampling procedure was used. Three Local Government Areas (LGAs) were randomly selected from the nine in Uyo, while three primary schools with high student enrolment were purposively selected (one from each LGA). Initial screening involved teacher nomination of underachieving primary five pupils in the classroom. Sixty PwLDs were selected after further screening using the Slosson Intelligence Test and the Pupil Rating Scale. The schools were randomly assigned to GDS (20), MLTS (20), and Control (20) groups. The instruments used were Slosson Intelligence Test (r=0.74), Pupils Rating scale (0.90), Mathematics Anxiety Scale for Children (r=0.92), Quantitative Reasoning Deficit Scale (r=0.88) and Quantitative Reasoning Achievement Test (r=0.75). Data were subjected to descriptive statistics, Analysis of covariance, and Scheffe Post-hoc test at 0.05 level of significance. The majority of the participants (57.0%) were female, and 62.0% had high mathematics anxiety. There was a significant main effect of treatment on QRSs (F(2;47)=17.67; partial =0.43). The participants exposed to GDS obtained the highest mean score (49.86), followed by those in MLTS (44.41) and those in the control group (32.05). There was a significant main effect of gender on QRSs (F(2;47)=9.34; partial = 0.00) in favour of males in GDS. There was a significant main effect of mathematics anxiety on QRSs (F(2;47)=7.97; partial =0.02). The participants with low mathematics anxiety had a higher mean score (39.62) than those with high mathematics anxiety (28.21). There was a significant interaction effect of treatment and mathematics anxiety on QRSs (F(2;47)=8.84; partial =0.08). The interaction effect of treatment and gender; gender and mathematics anxiety as well as the three way interaction effects were not significant. Guided discovery strategy, more than model-lead-test strategy, enhanced quantitative reasoning skills of pupils with learning disabilities in Uyo, Nigeria particularly among those with low mathematics anxiety. These strategies should be adopted by teachers in order to enhance quantitative reasoning skills of pupils with learning disabilities.